Equity fund flows and stock market returns in the US before and after the global financial crisis: A VAR-GARCH-in-mean analysis - Vassilios Babalos; Guglielmo Maria Caporale; Nicola Spagnolo (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The 2008-2009 global financial crisis has raised new questions about the relationship between equity fund flows and stock market returns. This paper analyses it using US monthly data over the period 2000:1-2015:08. A VAR-GARCH(1,1)-in-mean model with a BEKK representation is estimated, and a switch dummy for the global financial crisis is also included. We find causality-in-mean from stock market returns to equity fund flows (consistently with the feedback-trading hypothesis) only in the post-September 2008 period. There are also volatility spillovers from stock market returns to equity fund flows both before and after the crisis; however, this relationship is not stable, becoming weaker in the crisis period. As a robustness check we augment the model with a set of macroeconomic control variables. Their inclusion does not affect the main results.
Keywords: G23; C32; 330; Equity Fund Flows; Stock Market Returns; VAR-GARCH-in-mean model; Volatility